2020
DOI: 10.1074/mcp.ra119.001626
|View full text |Cite
|
Sign up to set email alerts
|

Proteomic Analysis Reveals that Topoisomerase 2A is Associated with Defective Sperm Head Morphology

Abstract: Male infertility is widespread and estimated to affect 1 in 20 men. Although in some cases the etiology of the condition is well understood, for at least 50% of men, the underlying cause is yet to be classified. Male infertility, or subfertility, is often diagnosed by looking at total sperm produced, motility of the cells and overall morphology. Although counting spermatozoa and their associated motility is routine, morphology assessment is highly subjective, mainly because of the procedure being based on micr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 81 publications
1
12
0
Order By: Relevance
“…Only a few studies have measured protein levels of low-quality spermatozoa (predictive of poor IVF outcomes) in comparison to high-quality spermatozoa, those finding many different proteins significantly more abundant in either of the groups (Netherton et al, 2018(Netherton et al, ,2020. Our study includes semen from samples used in IUI;…”
Section: Discussionmentioning
confidence: 99%
“…Only a few studies have measured protein levels of low-quality spermatozoa (predictive of poor IVF outcomes) in comparison to high-quality spermatozoa, those finding many different proteins significantly more abundant in either of the groups (Netherton et al, 2018(Netherton et al, ,2020. Our study includes semen from samples used in IUI;…”
Section: Discussionmentioning
confidence: 99%
“…Netherton et al analyzed nuclear extracts of human semen comparing high-and low-quality semen using LC-MS/MS and found that nuclear retention of specific proteins is a common facet among low-quality sperm cells. In particular, it was found that the presence of the enzyme topoisomerase 2A (TOP2A) in the sperm head is highly correlated to poor head morphology, and as a result, it could serve as a potential biomarker for confirming male infertility in clinical practice [62]. Vigodner et al researched the occurrence of the post-translational modification, sumoylation, in normal and abnormal sperm samples.…”
Section: Proteomics In Teratospermiamentioning
confidence: 99%
“…An interaction network was established according to the genes at the chromosome breakpoints in our patient (Figure 4). Interestingly, the genes for kinesin family member 20B (KIF20B), DNA topoisomerase III-alpha (TOP3A), LLGL scribble cell polarity complex component 1 (LLGL1), phosphoribosyl pyrophosphate synthetaseassociated protein 2 (PRPSAP2), and cell division cycle 45 (CDC45) were closely associated with DNA topoisomerase II alpha (TOP2A) expression, which has been found to be associated with the defective morphology of sperm heads (Netherton et al, 2020). As found in our patient, the shape of the sperm head is the most common morphological abnormality reported.…”
Section: The Impact Of Reciprocal Translocation On Genomic Instabilit...mentioning
confidence: 99%